Control of the optically induced heating of gold nanoparticles - Palermo, Giovanna; Caputo, Roberto; De Luca, Antonio; Umeton, Cesare Paolo (Photonics Letters of Poland, 2017)
Gold nanoparticles (GNPs) have proven to be good nano-sources of heat in the presence of specific electromagnetic radiation. This process, in fact, becomes strongly enhanced under plasmon resonance. In particular, the amount of generated heat and the consequent temperature increase depend on the number of GNPs that are collectively excited and on their relative distance. As a result, the regime of heat localization is deeply controlled by this last parameter. Full Text: PDF References Hutter, E., and Fendler, J. H. "Exploitation of localized surface plasmon resonance". Advanced Materials 16.19, 1685-1706 (2004) CrossRef Liz-Marzán, L. M., Murphy, C. J., & Wang, J. "Nanoplasmonics". Chemical Society Reviews, 43(11), 3820-3822 (2014). CrossRef Maier, S. A. "Plasmonics: fundamentals and applications". Springer Science & Business Media (2007). CrossRef Palpant, B. "Photothermal properties of gold nanoparticles. Gold nanoparticles in physics, chemistry and biology". Imperial College Press, London, (2012). DirectLink Baffou, G. and Quidant R. "Thermo-plasmonics: using metallic nanostructures as nanosources of heat". Laser & Photonics Reviews, 7(2):171?187, (2013). CrossRef Pelton, M., Aizpurua, J., & Bryant, G. "Metal?nanoparticle plasmonics". Laser & Photonics Reviews, 2(3), 136-159 (2008). CrossRef Kreibig, U., & Vollmer, M. "Optical properties of metal clusters" (Vol. 25). Springer Science & Business Media (2013). DirectLink J., Prashant K., S. Eustis, and M. A. El-Sayed. "Plasmon coupling in nanorod assemblies: optical absorption, discrete dipole approximation simulation, and exciton-coupling model." The Journal of Physical Chemistry B 110 (37) 18243-18253 (2006). CrossRef Jain, P. K., & El-Sayed, M. A. "Surface plasmon coupling and its universal size scaling in metal nanostructures of complex geometry: elongated particle pairs and nanosphere trimmers". The Journal of Physical Chemistry C, 112(13), 4954-4960 (2008). CrossRef Chapuis, P. O., Laroche, M., Volz, S., & Greffet, J. J. "Radiative heat transfer between metallic nanoparticles". Applied Physics Letters, 92(20), 201906 (2008). CrossRef Jain, P. K., & El-Sayed, M. A. "Plasmonic coupling in noble metal nanostructures". Chemical Physics Letters, 487(4), 153-164 (2010). CrossRef Cataldi, U., Caputo, R., Kurylyak, Y., Klein, G., Chekini, M. Cesare Umeton, C., Bürgi, T. "Growing gold nanoparticles on a flexible substrate to enable simple mechanical control of their plasmonic coupling". J. Mater. Chem. C, 2, 7927-7933 (2014). CrossRef